Fit for 90: Key elements of the EU’s climate policy infrastructure of the future - Trio, Wendel (Ökologisches Wirtschaften - Fachzeitschrift, 2026)
With its new 2040 target to cut emissions by 85 % – and 90 % including global action – the EU sets the stage for its next climate chapter. “Fit for 90” outlines five key steps to build a fair, ambitious policy framework for a climate-safe future beyond 2030.